Influence of the Meshing Phase Difference of Planetary Gear Transmission System in 2. 5MW Wind Turbine Gearbox on Its Inherent Frequency - Xue Dan; Wang Chunxiu; Mu Song; Jiang Chengsheng (Jixie chuandong)
A translational- torsional coupling dynamics model of planetary gear transmission on the low speed shaft in 2. 5 MW wind turbine gearbox is built by using lumped- parameter method. Through comparing the inherent frequency of the three planetary gears under the conditions of the mesh stiffness are equal and taking the same average mesh stiffness with the conditions of the different mesh stiffness which are influenced by meshing phase difference,the conclusion that the influence of different combination of mesh stiffness under the influence of meshing phase difference on the low inherent frequency is less,but have much more influence on the high inherent frequency is obained. This analysis of inherent frequencies laid a foundation for dynamics analysis of the planetary gear transmission system in 2. 5MW wind turbine.